Proximal palmar mini-incision carpal tunnel release technique - Al-Sudani, Abed F.; Al-Iedani, *, Mohammed S. (AL-Kindy College Medical Journal, 2015)
Background: Carpal tunnel syndrome is the most common entrapment neuropathy in humans today. For patients in whom conservative treatment fails, surgical decompression is indicated. Various surgical techniques are becoming increasingly popular. Due to the rapid postoperative recovery shown after endoscopic operations, proximal palmar mini-incision for carpal tunnel release is a comparative alternative.Methods: Ninety four patients [113 hands] with a carpal tunnel syndrome underwent carpal tunnel release through a 1-cm longitudinal incision made just over the distal flexor crease. The self- administered Boston Questionnaire was used to assess the severity of patients’ symptoms and their functional status, both before and after the surgical intervention and at their final follow-up. Patients were also asked, during the final follow-up, about the pain level of their scar tissue and functional outcome.Results: There was a significant decrease in the Boston Carpal Tunnel Questionnaire scores for the symptom severity scale and the functional status of patients in thisgroup, post- operatively at one month and at final follow – up. The mean operative time was significantly shorter than open or endoscopic CTR. After 1 month, only 4 hands[3.5%] stated they had scar tissue pain, no recurrence, short period return to work &cost effective.Conclusions: proximal mini-incision is as effective as ECTR. Furthermore, it is also a safe and simple procedure with shorter operative time& reduced surgical cost. The absence of relapse and good clinical results make this technique suitable